Legal Protection Against Cybercrime from Ransomware Attacks and Evaluation of the 2025 Cyber Security and Resilience Bill in Indonesia's Defense - Seri Mughni Sulubara; Virdyra Tasril; Nurkhalisah Nurkhalisah (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This research examines in-depth legal protection against cybercrime in Indonesia, with a specific focus on ransomware attacks. It also evaluates the 2025 Draft Cyber Security and Resilience Law (RUU KKS) as a measure to strengthen the national cyber defense system. The increase in ransomware cases targeting personal data, public institutions, and vital infrastructure has posed a serious threat to information security and national stability. Although the 2008 Electronic Information and Transactions Law (UU ITE) and the 2022 Personal Data Protection Law (UU PDP) serve as the legal basis, these two regulations do not yet specifically and comprehensively regulate ransomware. This results in challenges in law enforcement and victim protection, both in technical aspects, coordination, and human rights protection. The research method used is normative legal with a qualitative approach, which includes analysis of primary and secondary legal materials, as well as comparisons with regulations in several countries that have more mature ransomware handling mechanisms. The analysis of the 2025 Cyber Security Bill (RUU KKS) indicates that this draft regulation has the potential to strengthen the authority of cyber authorities, mandate reporting of cyber incidents, and impose stricter sanctions on perpetrators. However, implementing this policy requires effective cross-agency coordination, transparent oversight, and synergy between the public and private sectors. This study concludes that the 2025 Cyber Security Bill (RUU KKS) represents a strategic step in building a national cybersecurity system that is adaptive, integrated, and responsive to evolving cyber threats. However, its success will depend heavily on improving public digital security literacy, multi-sectoral collaboration, investment in detection and prevention technology, and guaranteeing human rights protection. These findings are expected to provide input for policymakers in formulating comprehensive and sustainable cybersecurity regulations as a bulwark of national defense in the digital era.